2007
DOI: 10.1007/s00424-007-0224-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of HCN channels

Abstract: Hyperpolarization-activated cation currents termed I (f/h) are observed in many neurons and cardiac cells. Four genes (HCN1-4) encode the channels underlying these currents. New insights into the pathophysiological significance of HCN channels have been gained recently from analyses of mice engineered to be deficient in HCN genes. Lack of individual subunits results in markedly different phenotypes. Disruption of HCN1 impairs motor learning but enhances spatial learning and memory. Deletion of HCN2 results in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…For example, HCN1 regulates motor learning and spatial memory (Nolan et al, 2003(Nolan et al, , 2004, while HCN2 regulates thalamic excitability associated with absence seizures Ying et al, 2007b). The function of brain HCN3, however, has remained elusive (Herrmann et al, 2007). HCN channel gating is controlled by both ligand and voltage Biel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, HCN1 regulates motor learning and spatial memory (Nolan et al, 2003(Nolan et al, , 2004, while HCN2 regulates thalamic excitability associated with absence seizures Ying et al, 2007b). The function of brain HCN3, however, has remained elusive (Herrmann et al, 2007). HCN channel gating is controlled by both ligand and voltage Biel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…HCN1 promotes the ability to learn new motor tasks, but it inhibits spatial learning and memory 30 . HCN2 plays an important role in the regulation of cellular excitability, motion control and synus node functioning because its knockout results in absence epilepsy, ataxia and sinus node dysfunction 31 . HCN4 is vital for cardiac development; its knockout fails to have sinoatrial node-like action potential in mice and such knockouts are embryonic lethal [31][32][33] .…”
Section: Physiology and Functions Of Hcnmentioning
confidence: 99%
“…Recently, the role of HCN channels in depression is also coming to the fore 36,81 . Reduction of HCN channels in thalamus and cortex (through TRIP8b knockout) results in a model of absence epilepsy 82 and recent work has shown these channels to be a good drugable targets for epilepsy treatment 31,83,84 . Auditory roles of these channels are also becoming clearer with new information, with the latest study showing their crucial role in tinnitus too 85 .…”
Section: Recent Studies and Future Directionsmentioning
confidence: 99%
“…Changes to a number of ion channel currents may result in electrical remodeling, including the L-type calcium current, the transient outward potassium current when downregulated and the inward rectifier potassium current when upregulated (6). Previous studies have found that the hyperpolarization current (I f ) is associated with atrial electrical remodeling in patients with AF (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular propagators of the I f current are hyperpolarization-activated cyclic nucleotide-gated (HCN) channels (11). Therefore, the inhibition of HCN channels has become a focus of study for the treatment of arrhythmia (6). However, few studies have investigated changes in the expression of HCN channel isoforms in atrial cells following AF.…”
Section: Introductionmentioning
confidence: 99%